Politeness and pseudo-intimacy in a food radio call-in program. (March 2018) - Matwick, Kelsi; Matwick, Keri
Highlights: Small talk, expressions of gratitude, humor and compliments construct pseudo-intimacy on a food radio call-in. Politeness strategies are used to save hosts' and callers' face on food radio through alignment. Food radio is a form of "mediated cookery". Food talk in call-in radio program compares to a sociable argument. Abstract: Food radio call-in program offers a mediated public forum for home cooks to ask experts culinary questions. Both the expert host and the caller risk face; the expert host must be able to answer the caller to save his reputation and business, and the caller does not want be seen as an inept home cook. In a case study of an American food radio and podcast, this article proposes that a pseudo-intimacy is created by both the host and callers through interactional and politeness strategies including small talk, expressions of gratitude, humor, and compliments. It is argued that pseudo-intimacy mitigates judgment of the expert host and alleviates the fears of home cooks. Ultimately, the food radio call-in exchange positively frames home cooking, which opens up the conversation and cooking to all listeners.